Sharia Compliance through Non-Halal Income: The Influence of the Sharia Supervisory Board, Independent Commissioners, and Institutional Ownership in Indonesian Islamic Commercial Banks (2014–2024) - Gurnita, Ligar; Setiawan, Iwan; Hadiani, Fatmi; Arsyah, Teguh Dwi; Qolbi, Satria Kharimul (Journal of Applied Islamic Economics and Finance, 2025)
Sharia compliance is a cornerstone for Islamic Commercial Banks (ICBs), yet minimizing non-halal income as a compliance indicator remains crucial. This study analyzes the influence of Sharia Supervisory Board (SSB) quantity, independent commissioner composition, and institutional ownership on non-halal income in 10 Indonesian ICBs (2014-2024). Employing panel data regression with a Fixed Effect Model (FEM), the results indicate that SSB quantity significantly and positively affects non-halal income, suggesting that increased SSB numbers correlate with decreased sharia compliance. Conversely, independent commissioner composition and institutional ownership show no significant influence. These findings bear important implications for strengthening ICBs' sharia governance, particularly in re-evaluating the quantitative role effectiveness of the SSB. This study fills a literature gap by providing empirical evidence on factors affecting non-halal income, while encouraging further research into other sharia governance factors.